HUBUNGAN KEDISIPLINAN GURU DENGAN MINAT BELAJAR SISWA PADA PEMBELAJARAN SKI DI MTS MANUNGGAL BANDAR KHALIPAH - Jihan Emelia Sari; Wahyudin Nur Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine: (1) Teacher Discipline at MTs Manunggal Bandar Khalipah, (2) Student Learning Interest in SKI Learning at MTs Manunggal Bandar Khalipah, (3) Relationship between Teacher Discipline and Student Learning Interest in SKI Learning at MTs Manunggal Bandar Khalipah. This research uses a quantitative approach with a correlational method. The data collection technique in this study was using a questionnaire. Data were obtained through valid and reliable instruments. The results of the analysis show that teacher discipline is in the good category, with a reliability value of 0.834. Student learning interest is also in the high enough category, with a reliability value of 0.847. The linearity test showed a linear relationship between teacher discipline and student learning interest with a significance value of 0.179 (> 0.05). However, the correlation test showed a positive but not statistically significant relationship with a Pearson Correlation value of 0.206 and p = 0.275 (> 0.05). The normality test showed that the data approached normal distribution based on the Shapiro-Wilk test. This study concludes that teacher discipline has not had a significant effect on student interest in learning, so other factors need to be explored further to increase student interest in learning.